Parkett : Cao Fei, Omer Fast, Adrian Ghenie, Lynette Yiadom-Boekye. - Beckwith, Naomi; McDonough, Tom; Zhuang, Jiayun; Hanru, Hou; Bradley, Rizvana; Edwards, Adrienne; Als, Hilton; Scranton, Roy; Wilson-Goldie, Kaelen; Lütticken, Sven; Mircan, Mihnea; Hudson, Suzanne; et al. (Zürich : Parkett-Verlag, 2017)
Fei, Cao ; Fast, Omer ; Ghenie, Adrian ; Yiadom-Boekye, Lynette
boek